2022
DOI: 10.3389/fnagi.2022.845053
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Tea Drinking and Cognitive Disorders in Older Adults: A Meta-Analysis of Observational Studies

Abstract: IntroductionPrevious research has shown that tea drinking has a bearing on Cognitive Disorders, but the conclusions are inconsistent. The purpose of this research was to systematically assess the published evidence pertaining to tea drinking and the risk of cognitive disorders in older adults using a meta-analysis, and to concurrently evaluate the dose-response association.DesignA meta-analysis.Setting and ParticipantsWe used the PubMed and Web of Science databases for a literature search until 30 May 2021. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The total catechin levels are reduced from 35−50% in green tea to 10% in black tea [ 43 ]. Meta-analyses results have suggested that the cognitive benefits of tea (green, black) may increase with increasing daily consumption [ 47 , 48 , 49 ]. Another study [ 9 ] reported a cognitive protective effect of black tea consumption.…”
Section: Discussionmentioning
confidence: 99%
“…The total catechin levels are reduced from 35−50% in green tea to 10% in black tea [ 43 ]. Meta-analyses results have suggested that the cognitive benefits of tea (green, black) may increase with increasing daily consumption [ 47 , 48 , 49 ]. Another study [ 9 ] reported a cognitive protective effect of black tea consumption.…”
Section: Discussionmentioning
confidence: 99%
“…[63] Phenolic acids are consumed through common foods, such as nuts, apple, coffee, and tea. Although data specifically on phenolic acid intake and cognitive outcomes are scarce, there is some evidence in the scientific literature that consumption of walnuts, [64] coffee, [65] and tea [66] was associated with lower odds of cognitive decline, despite no acute effects on established cognitive dysfunction. [67] From a mechanistic point of view, phenolic acids demonstrate an excellent capacity to pass through the blood-brain barrier and exert potential direct activity on the human brain.…”
Section: Polyphenol Classmentioning
confidence: 99%